ANALISIS USAHA BUDIDAYA IKAN KERAPU (sarranidae) DALAM KERAMBA JARING APUNG (KJA) DI TANJUNG LIMAU KELURAHAN BONTANG BARU KECAMATAN BONTANG UTARA KOTA BONTANG - Muhammad Rizky Irma Perdana; Nurul Ovia Oktawati; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2017)
The purpose of research were to analysis the feasibility study and channel marketing of grouper farming in floating net cages in Tanjung Limau. This study was conducted for 7 months starting from september 2016 to March 2017. The determination of the sample based on the census method with the amount respondents smaller than thirty people. The main data is obtained from the groupers by interviewing how to use questionnaires. Data were analyzed using Revenue Cost Ratio. the results of the analysis show the value as follows the average valve of Revenue Cost Ratiois 2.99 means that the income earned 2.99 times of expenditure, Therefore, grouper farming in Tanjung Limau feasibel to be implemented. The profit of respondents is an average of Rp.7.071.622.00,-/month/person.